REVITALIZATION OF THE PROSECUTOR'S OFFICE IN BUILDING A FAIR JUSTICE SYSTEM - Lulu Padilah Pratama; Rista Tiara Maharani; Icha Rahma Nurul Afni; Waluyadi Waluyadi (Ann Publisher, 2025)
Abstract: Background. As a law enforcement institution, the prosecutor's office has a central role in upholding the rule of law, ensuring justice, and protecting the rights of the public. However, in practice, some challenges, such as low professionalism, lack of transparency, and the influence of political and economic interests, can hinder the prosecutor's office's performance in enforcing the law objectively. Aims. This research analyzes the approach to revitalizing the prosecutor's office, including institutional aspects and improving the supervision system. Methods. This study uses a Normative approach. This research for data collection was obtained from the analysis of legal documents, laws and regulations, and academic journals. Result. The results of the study show that the revitalization of the prosecutor's office through reform of the recruitment system also found that challenges such as political intervention, lack of qualified human resources, and lack of coordination with other judicial institutions are still obstacles in realizing an independent and professional prosecutor's office. Conclusion. This research shows that strengthening accountability, improving the professionalism of prosecutors, and utilizing technology in legal administration can accelerate fair judicial reform. In contrast to previous studies that emphasized the institutional aspect of the judiciary in general, this study highlights the central role of the prosecutor's office in ensuring that the legal process runs objectively and independently. Implementation. Revising the prosecutor's office is a strategic step to build a fairer and more transparent judicial system. Therefore, revitalizing the prosecutor's office needs to be focused not only on structural reforms but also on innovations in governance and increasing public trust in the legal system.